Role of non-rational factors in the two levels of decision making. - Low, Eng Chiew. (2012)
We make choices so frequently in life that the complexity of decision making seldom occurs to us. Nonetheless, when we face problems in making choices, the question of what may influence our decision making process surfaces. The decision making process occur on two levels. Adapting from Evans’ (2008, 2010b) terminologies, the two levels are Type 1 automatic processing, or intuition, and Type 2 effortful processing, or reasoning. These two levels of decision making are influenced by a combination of rational and non-rational factors, often rendering the final decisions made less than rational. However, the influence of these factors, especially non-rational ones, is not entirely detrimental to our decision making process (Damasio, 1994). In this paper, we briefly explore how rational factors like cognitive ability, brain development and working memory capacity affect decision making. These brief discussions about rational factors are necessary so as to allow better integration and understanding of the role that non-rational factors play in decision making. Our main focus of non-rational factors is on knowledge, personality and emotion. As it is well-established that explanations of the decision making process by focusing merely on rationality is not realistic (Kahneman, 2003; Kahneman & Klein, 2009), we see that the abovementioned non-rational factors do, indeed, interact with rational factors or override rational factors to influence our choices via the two levels of decision making.